The Lighthouse and the observatory : Islam, science, and empire in late Ottoman Egypt - Stolz, Daniel A. (Science in history)
Astronomy and science in Ottoman era Egypt, as partly influenced by the publication The Lighthouse, and in scientific research of the time.